القوانين الأساسية الخاصة دراسة حالة سلك الأمن الوطني - • شرحرح زكرياء (جامعة المسيلة, 2022)
إن دراسة القوانين الأساسية الخاصة بموضوع الوظيفة العمومية عموما وسلك الأمن الوطني خصوص من المواضيع المهمة التي تعكس قدرة الدولة وتحكمها في إداراتها وقدرتها أيضا على تجسيد خططها التنموية في جميع القطاعات وعليه كان موضوع القوانين الاساسية الخاصة التي تسير سلك الأمن الوطني محور دراسات عديدة تناولت كل الجوانب المتعلقة بالوظيفة العمومية، لذا فإن هذه المذكرة تبحث أساسا في تناول موضوع ذا صلة بفلسفة المشرع إبتدءا والقائمة على تسيير هذا القطاع التابع لمنظومة الوظيفة العمومية، وإحداث قطيعة حقيقية مع كل النصوص المنظمة للوظيفة العمومية من قبل، وهذا من خلال تكريس المبادئ التقليدية القائمة عليها الوظيفة العمومية والإنفتاح على حقائق جديدة تدعم عملية الإصلاح والنهوض بالوظيفة العمومية خاصة ما يتعلق في الجانب الأمني من خلال مختلف القوانين الخاصة التي تسير هذا القطاع لتكون بحق الوجه العاكس لقدرة الدولة على التنظيم والتحكم في سياساتها بالإضافة إلى إيجاد نصوص تنظيمية تؤطر ميدان الوظيفة العمومية لمنحها هامشا أوسع من المرونة . الكلمات المفتاحية: القوانين الأساسية، الوظيفة العمومية، الأمن الوطني Abstract: The study of the basic laws on the subject of the public service in general and the national security corps in particular is one of the important topics that reflects the state’s ability and control over its administration and its ability to also embody its development plans in all sectors. Therefore, the subject of the special basic laws that run the national security corps was the focus of many studies that dealt with all aspects related to Therefore, this memorandum mainly discusses a topic related to the philosophy of the legislator from the beginning, which is based on the management of this sector of the public service system, and a real break with all the texts regulating the public service before, and this is by dedicating the traditional principles on which the public service and openness are based. On new facts that support the process of reform and the advancement of the public service, especially with regard to the security aspect, through the various special laws that govern this sector to be the true reflection of the state’s ability to organize and control its policies, in addition to finding regulatory texts that frame the field of the public service to give it a wider margin of flexibility. Key words: basic laws, public service, national security
Keywords: القوانين الأساسية، الوظيفة العمومية، الأمن الوطني